Incidence of a new proposal syllabus for teaching aeronautical phraseology in english at Cap. Fernando Vasconez Army Aviation School for XXIX basic pilots course 2006 - Armas Miranda, Verónica Karina (2007)
Differences in the use of ICAO (International Civil Aviation Organization) phraseology in some countries complicate understanding; especially to pilots whose English is an acquired language. United States and Canada form a region where such differences are mostly noticeable. Effective communication starts with the knowledge and respect of ATC procedures and aircraft performance data. Effective radio communication abroad also requires proficiency in general English. A well-known saying ¿Seeing once is better than hearing twice¿ gives the worst fit when it concerns radiotelephony phraseology. While preparing for flights in the North America and looking through materials that were at hand, there was no expectation of a bolt from the blue. But the first landing at Gander, followed by Ottawa, Toronto, Boston, New York, Chicago, Andrews and McGuire Air Force Bases, have made it clear that what was read by eyes in a book was rather difficult for ears to hear. A deeper study of American aviation regulations has shown that radio communication over the US was a trouble not only to the crews, but also to American regulating authorities and aviation industry. In the fall of 1988 the FAA (Federal Aviation Administration) and airlines called for a joint action to improve communications between pilots and controllers.